Short-term effects of particulate matter during desert and non-desert dust days on mortality in Iran. (January 2020) - Shahsavani, Abbas; Tobías, Aurelio; Querol, Xavier; Stafoggia, Massimo; Abdolshahnejad, Mahsa; Mayvaneh, Fatemeh; Guo, Yuming; Hadei, Mostafa; Saeed Hashemi, Seyed; Khosravi, Ardeshir; Namvar, Zahra; Yarahmadi, Maryam; et al.
Graphical abstract: Highlights: Desert dust episodes were more intense and frequent in Ahvaz than in Tehran. The effect of PM10 in mortality was higher for dust than non-dust days in Ahvaz. In Tehran the PM10 effect was slightly higher during non-dust days. Effects were evidenced for PM2.5 only in Tehran for non-dust days at lags 2 and 3. Middle East desert dust is an important risk factor to human health in this region. Abstract: Background: Increased atmospheric particulate matter (PM) concentrations are commonly observed during desert dust days in Iran, but there is still no evidence of their effects on human health. We aimed to evaluate the association between daily mortality and exposure to PM10 and PM2.5 during dust and non-dust days in Tehran and Ahvaz, two major Middle Eastern cities with different sources, intensity, and frequency of desert dust days. Methods: We identified desert dust days based on exceeding a daily PM10 concentration threshold of 150 µg/m 3 between 2014 and 2017, checking for low PM2.5 /PM10 ratio typical of dust days. We used a time-stratified case-crossover design to estimate the short-term effects of PM10 and PM2.5 concentrations on daily mortality during dust and non-dust days. Data was analyzed using conditional Poisson regression models. Results: Higher concentrations of PM and frequency of desert dust days were observed in Ahvaz rather than Tehran. In Ahvaz, the effect of PM10 at lag 0 was much higher during dust days, an increment of 10 μg/m 3 was associated with 3.28% (95%CI = [2.42, 4.15]) increase of daily mortality, than non-dust days, 1.03% (95%CI = [−0.02, 2.08]), while in Tehran, was slightly higher during non-dust days, 0.72% (95%CI = [0.23, 1.23]), than in dust days, 0.49% (95%CI = [−0.22, 1.20]). No statistically significant associations were observed between PM2.5 and daily mortality in Ahvaz, while in Teheran the effect of PM2.5 increased significantly during non-dust days at lag 2, 1.89% (95%CI = [0.83, 1.2.95] and lag 3, 1.88% (95%CI = [0.83, 1.2.95]). Conclusion: The study provides evidence that exposure to PM during Middle East dust days is an important risk factor to human health in arid regions and areas affected by desert dust events.